HigA2 (Rv2021c) Is a Transcriptional Regulator with Multiple Regulatory Targets in Mycobacterium tuberculosis - Mingyan Xu; Meikun Liu; Tong Liu; Xuemei Pan; Qi Ren; Tiesheng Han; Lixia Gou (Microorganisms, 2024)
Toxin-antitoxin (TA) systems are the major mechanism for persister formation in Mycobacterium tuberculosis (Mtb). Previous studies found that HigBA2 (Rv2022c-Rv2021c), a predicted type II TA system of Mtb, could be activated for transcription in response to multiple stresses such as anti-tuberculosis drugs, nutrient starvation, endure hypoxia, acidic pH, etc. In this study, we determined the binding site of HigA2 (Rv2021c), which is located in the coding region of the upstream gene higB2 (Rv2022c), and the conserved recognition motif of HigA2 was characterized via oligonucleotide mutation. Eight binding sites of HigA2 were further found in the Mtb genome according to the conserved motif. RT-PCR showed that HigA2 can regulate the transcription level of all eight of these genes and three adjacent downstream genes. DNA pull-down experiments showed that twelve functional regulators sense external regulatory signals and may regulate the transcription of the HigBA2 system. Of these, Rv0903c, Rv0744c, Rv0474, Rv3124, Rv2603c, and Rv3583c may be involved in the regulation of external stress signals. In general, we identified the downstream target genes and possible upstream regulatory genes of HigA2, which paved the way for the illustration of the persistence establishment mechanism in Mtb.